Stepwise isolation of low-valent, low-coordinate Sn and Pb mono- and dications in the coordination sphere of platinum - Braunschweig, Holger; Celik, Mehmet Ali; Dewhurst, Rian D.; Heid, Magdalena; Hupp, Florian; Sen, Sakya S. (Chemical Science, 2015)
Synthetic access to low-coordinate Pb mono- and dications is in general impeded due to their poor solubility and highly electrophilic nature. However, the electrophilicity of these cations can be tamed by attaching them to electron-rich transition metals. Following this principle we have isolated low-valent Pb mono- ([(Cy3P)(2)Pt-PbCl](2)[AlCl4](2), 8a) and dications ([(Cy3P)(2)Pt(Pb)][AlCl4](2), 11) in the coordination sphere of platinum. The same approach then has been implemented for the isolation of analogous low-valent Sn mono- (7a) and dications (10). An energy decomposition analysis (EDA-NOCV) was performed to investigate the nature of Pt-Pb and Pb-Cl bonding in [(Cy3P)(2)Pt(PbCl2)] (2), 8a and 11. The results show that the Pt-Pb bonds in 8a and 11 are electron-sharing in nature, whereas that of the precursor 2 is a dative bond. The breakdown of attractive interactions in 2, 8a and 11 reveals that the ionic interactions in the analyzed Pt-Pb and Pb-Cl bonds are always stronger than the covalent interactions, except for the Pb-Cl bond in 8a. The calculated D3 dispersion energies show that dispersion interactions play a key role in the thermodynamic stability of 2, 8a and 11.

Dynamic, reversible oxidative addition of highly polar bonds to a transition metal - Bertermann, Ruediger; Boehnke, Julian; Braunschweig, Holger; Dewhurst, Rian D.; Kupfer, Thomas; Muessig, Jonas H.; Pentecost, Leanne; Radacki, Krzysztof; Sen, Sakya S.; Vargas, Alfredo (Journal of the American Chemical Society, 2016)
The combination of Pt complexes and indium trihalides leads to compounds that form equilibria in solution between their In X oxidative addition (OA) products (Pt indyl complexes) and their metal-only Lewis pair (MOLP) isomers (LnPt -> InX3). The position of the equilibria can be altered reversibly by changing the solvent, while the equilibria can be reversibly and irreversibly driven toward the MOLP products by addition of further donor ligands. The results mark the first observation of an equilibrium between MOLP and OA isomers, as well as the most polar bond ever observed to undergo reversible oxidative addition to a metal complex. In addition, we present the first structural characterization of MOLP and oxidative addition isomers of the same compound. The relative energies of the MOLP and OA isomers were calculated by DFT methods, and the possibility of solvent-mediated isomerization is discussed.